Entrepreneurial Empowerment of Santri: A Systematic Literature Review on Economic Self-Reliance in Pesantren - Kusuma Wisudawan, Anja; Khairullah; Rosidi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines santri empowerment in fostering economic independence within Islamic boarding schools (pesantren) by employing a systematic literature review approach. The study aims to synthesize existing research and to identify key factors influencing the success of empowerment initiatives. Data were collected from peer-reviewed journal articles published between 2020 and 2025, primarily sourced from Google Scholar using the Publish or Perish software. After applying inclusion and exclusion criteria, six relevant studies were ultimately selected for in-depth analysis. The findings reveal that santri empowerment is a multidimensional process that is shaped by several interconnected factors. First, the integration of entrepreneurship education into pesantren curricula plays a crucial role in developing santri’s entrepreneurial mindset and practical skills. Second, the leadership of kiai and institutional support significantly influence the sustainability of empowerment programs. Third, multi-stakeholder collaboration, including government and alumni involvement, enhances access to critical resources and market opportunities. Fourth, digital transformation, particularly through e-commerce, expands business reach and competitiveness. Finally, empowerment initiatives based on local economic potential contribute to sustainable development and community impact. This study concludes that pesantren have significant potential to function as centers of community-based economic empowerment. The study contributes to the conceptual understanding of santri empowerment and provides insights for developing integrated and adaptive empowerment models. Future research is recommended to adopt empirical approaches to validate these findings in diverse pesantren contexts.